2022
DOI: 10.3389/fped.2022.881908
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-infectious Bronchiolitis Obliterans in Children: A Systematic Review and Meta-Analysis

Abstract: BackgroundPost-infectious bronchiolitis obliterans (PIBO) is a long-term sequela after an initial insult to the lower respiratory tract. A comprehensive understanding of the factors that contribute to a high risk of developing PIBO is important to help define therapeutic strategies and improve prognosis.MethodsWe performed a systematic review of published literature available in the online databases including PubMed, Embase, Web of Science, CNKI, Wan Fang, and VIP, with the last search updated on 27 January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Li et al 19 found that inpatient days indicated a statistically significant difference between the PIBO and non-PIBO group, and the mean length of hospital stay was 16.3±10.6 days in children with PIBO compared with 10.9±8.2 days in the non-PIBO group. This is similar to our findings, which showed that the mean length of hospital stay was 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days in the PIBO group compared to 10 (7-13) days in the non-PIBO group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Li et al 19 found that inpatient days indicated a statistically significant difference between the PIBO and non-PIBO group, and the mean length of hospital stay was 16.3±10.6 days in children with PIBO compared with 10.9±8.2 days in the non-PIBO group. This is similar to our findings, which showed that the mean length of hospital stay was 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days in the PIBO group compared to 10 (7-13) days in the non-PIBO group.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that age was a risk factor for predicting PIBO; hence, children tended to develop PIBO at a lower age. A meta-analysis by Liu et al 16 showed that compared with older children, younger children were more likely to develop PIBO, and most PIBO patients were younger than 3 years. Huang found that the average age at PIBO diagnosis was 17.71 (7-91) months.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, glucocorticoids, gamma globulin, bacterial co-infection, and a history of wheezing and male are also considered to be among the contributing factors. [ 50 ] Lactatedehydrogenase levels, pleural effusion, hypoxemia, gender, and mechanical ventilation have been noted as risk factors for PIBO in Korean patients. [ 51 ] Persistent wheezing and acute respiratory failure in Chinese children with adenovirus pneumonia is an independent risk factor for PIBO.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%
“…No reports of serious short-term complications, such as postinfectious chronic lung disease, have been documented in severe cases of HBoV1 ALRI, in contrast to adenovirus, influenza and Bordetella pertussis. 70,71 However, the association between HBoV1 and medium or long-term recurrence of wheezing remains unknown.…”
Section: Natural History Of Infection Pathophysiology and Clinical Fe...mentioning
confidence: 99%